2009
DOI: 10.1590/s0034-89102009000300014
|View full text |Cite
|
Sign up to set email alerts
|

Fidedignidade de rótulos de alimentos comercializados no município de São Paulo, SP

Abstract: OBJECTIVE:To assess reliability of information about nutritional facts stated on labels of industrialized foods. METHODS:A total of 153 industrialized foods, usually consumed by children and adolescents and marketed in the city of São Paulo, Southeastern Brazil, between 2001 and 2005, were analyzed. Nutrient contents stated on labels were compared to the results obtained from offi cial (physical-chemical) analytical methods, considering the 20% variability tolerated by the current legislation to approve or rej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
18

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 10 publications
1
8
0
18
Order By: Relevance
“…Other studies found differences in sodium contents in excess of 20% in 5 (50%) pastas 19 and 64 (57%) snack and potato chips 20 , corroborating the results of the present study. These excessive differences show that it is essential to effectively survey all nutrition information reported on the labels to check their accuracy, allowing well-informed Comparison of the sodium contents reported on the labels with those determined analytically shows that the differences between both are significant (p<0.05) in 12 samples analyzed by flame photometry and 6 samples analyzed by chloride titration.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies found differences in sodium contents in excess of 20% in 5 (50%) pastas 19 and 64 (57%) snack and potato chips 20 , corroborating the results of the present study. These excessive differences show that it is essential to effectively survey all nutrition information reported on the labels to check their accuracy, allowing well-informed Comparison of the sodium contents reported on the labels with those determined analytically shows that the differences between both are significant (p<0.05) in 12 samples analyzed by flame photometry and 6 samples analyzed by chloride titration.…”
Section: Discussionsupporting
confidence: 92%
“…Entende-se por rotulagem nutricional toda inscrição destinada a informar ao consumidor sobre as propriedades nutricionais de um alimento, a qual deve compreender a declaração do valor energética e nutriente e a declaração das propriedades nutricionais (informação nutricional complementar) 5 . Para que o consumidor possa utilizar esta ferramenta é preciso que a veracidade das informações apresentadas pelo rótulo nutricional em alimentos seja garantida, cumprindo assim o objetivo de auxiliar ao consumidor em suas escolhas e aos profissionais de saúde, na orientação para a composição da dieta 6 . Diversos estudos apontam não conformidades entre dados descritos na rotulagem nutricional e a real composição do alimento fazendo com que o consumidor se sinta enganado [6][7][8][9][10][11][12][13] .…”
Section: Introductionunclassified
“…We also observed a lack of studies in the literature about Na levels in Brazilian processed foods (21)(22)(23) , especially those targeted at children and adolescents (24,25) . Therefore, the present study assessed the Na levels and serving sizes reported on the labels of processed foods sold in Brazil that are usually consumed as snacks by children and adolescents.…”
mentioning
confidence: 98%